14, 15‐epoxyeicosatrienoic acid promotes production of brain derived neurotrophic factor from astrocytes and exerts neuroprotective effects during ischaemic injury. (6th January 2016) - Yuan, L.; Liu, J.; Dong, R.; Zhu, J.; Tao, C.; Zheng, R.; Zhu, S.
Abstract : Aims: 14, 15‐Epoxyeicosatrienoic acid (14, 15‐EET) is abundantly expressed in brain and exerts protective effects against ischaemia. 14, 15‐EET is hydrolysed by soluble epoxide hydrolase (sEH). sEH −/− mice show a higher level of 14, 15‐EET in the brain. Astrocytes play a pivotal role in neuronal survival under ischaemic conditions. However, it is unclear whether the neuroprotective effect of 14, 15‐EET is associated with astrocytes. Methods: A mouse model of focal cerebral ischaemia was induced by middle cerebral artery occlusion. Oxygen–glucose deprivation/reoxygenation (OGD/R) was performed on cultured murine astrocytes, neurons and a human cell line. Cell viabilities were measured by 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2H‐tetrazolium bromide (MTT) assay. The mRNA expressions were quantified by real‐time PCR. Brain derived neurotrophic factor (BDNF) concentration was measured by ELISA. Protein expressions were quantified by Western blotting. BDNF and peroxisome proliferators‐activated receptor gamma (PPAR‐γ) expressions were analysed by confocal microscopy. Results: Decreased infarct volumes, elevated BDNF expression and increased numbers of BDNF/GFAP Glial Fibrillary Acidic Protein double‐positive cells were observed in the ischaemic penumbra of sEH −/− mice. The decreased infarct volumes of sEH −/− mice were diminished by intracerebroventricular injection of a blocker of BDNF receptor. 14, 15‐EET increases BDNF expression and cell viability of murine astrocytes and U251 cells by BDNF‐TrkB Tyrosine receptor kinase‐B‐extracellular signal‐regulated kinase 1/2 signalling during OGD/R. 14, 15‐EET protects neurons from OGD/R by stimulating the production of astrocyte‐derived BDNF. 14, 15‐EET stimulates the production of astrocyte‐derived BDNF through PPAR‐γ/p‐cAMP‐response element binding protein signal pathways. Conclusions: Our study demonstrates the importance of 14, 15‐EET‐mediated production of astrocyte‐derived BDNF for enhancing viability of astrocytes and protecting neurons from the ischaemic injury and provides insights into the mechanism by which 14, 15‐EET is involved in neuroprotection. Abstract : Using mouse and cell culture models this study demonstrates that in an ischaemic environment 14, 15‐EET promotes production of astrocyte‐derived BDNF enhancing astrocyte viability and contributing to neuroprotection.